Impact Assessment of Elevation Angles on Signal Propagation at VHF and UHF Frequencies for Improved Rural Telephony - Ukommi, Ubong; Ubom, Emmanuel (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
Rural telephony is challenging in the remote part of Nigeria due to inadequate telecommunication infrastructure, exorbitant cost of communication systems and poor road network for extension of fiber network. These factors constitute poor or no cellular network services in many villages. Alternatively, using Television White Space (TVWS) technology to facilitate telephony services in the rural areas through Ultra High Frequency (UHF) and Very High Frequency (VHF) spectrum is cost effective. Thus, this research investigates impact of elevation angle on signal propagation at UHF/VHF frequencies. The experimental test scenarios took measurements of received signal quality performance at different elevation angles and transmit power levels to obtain more stable results for substantive inference. The experimental test scenario considered a communication link, operating at UHF frequency of 436 MHz. During the experiment, azimuth and propagation loss for the communication link were kept constant while the receiving antenna elevation angles were varied to assess the impact of elevation angles. The assessment examined results obtained during the experiment. Comparing the received signal quality performance at zero (00) elevation angle, it has been observed that the received signal quality improves when the transmit power allocation increases. Results further show that for a given transmit power level of 34dBm, at zero (00) elevation angle test configuration, received signal quality performance of 1.80 dB, 6.90 dB at 300 elevation angle and 10.9 dB at 600 elevation angle were obtained, compared to improved quality performance of 11.8 dB at 00 elevation angle, 19.90 dB at 300 elevation angle and 24.92 dB at 600 elevation angle when the transmit power level was increased to 46.98 dBm. It is deduced from the experimental results that elevation angle of receiving antenna has significant influence on the received signal quality performance. This insight is very useful in the design and network planning of rural telecommunication services using TVWS frequencies for improved rural broadband penetration.